Triaxial Test and Mechanical Analysis of Rock-Soil Aggregate Sampled from Natural Sliding Mass - Shuling Huang; Xiuli Ding; Yuting Zhang; Wei Cheng (Advances in Materials Science and Engineering)
Rock-soil aggregate, as a specific geomaterial, exhibits complicated mechanical behavior. The rock-soil aggregate sampled from the deep layer of sliding mass at Jinpingzi area of Wudongde hydropower plant on Yangtze River is investigated to understand its mechanical behavior. Large-scale laboratory triaxial tests are conducted considering different gradations, stone contents and confining pressures. The results show that variation of stone content and gradation considerably affects the mechanical characteristics of rock-soil aggregate. Further, the influences of stone content, and gradation variation on stress-strain curve, Mohr-Coulomb criterion based shear strength parameters, Duncan-Chang model based deformation parameters, and internal friction angle are analyzed. A modified Rowe’s stress-dilatancy equation describing the mechanical response of rock-soil aggregate is then suggested.